Penerapan Metode FLASH Dalam Pembelajaran Tahfidz Quran Juz “Amma Untuk Siswa MTs Madani Perdagangan II Kabupaten Simalungun - Nurfitriani, Rahmah; Almi Hidayat, M (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2024)
Tahfidz learning at MTs Madani Perdagangan II uses the FLASH method which can make students memorize verses of the Quran quickly and easily. The aim of this research is to find out how the FLASH method is applied in teaching tahfidz and some of the obstacles faced by teachers in teaching tahfidz using the FLASH method. This research method uses a case study method and a qualitative approach. The results of the research show that the application of the FLASH method is by, Focus (F) “Fokus” listening to the chanting of the verse, Look (L) “Lihat” at the writing of the verse, Let's read (A) “Ayo Baca” at the writing of the verse, Visual Symbols (S)”Simbol Visual” are paid attention to to understand the meaning and significance of the memorized verse and make connections. (H) “Hubungkan” visual symbols and meaning of verses using hand and facial movements. The obstacle for teachers in implementing this method is that they cannot correct students' recitations one by one because they only have two hours per week, so they can correct students' recitation The next obstacle is the limitations of the Juz Amma FLASH method memorization book which can only be used in groups, so students write memorized verses and pictures in their notebooks to repeat the memorization at home.